The Influence of Financial Literacy, Amount of Pocket Money, and Life Style on Student Consumption Behavior STKIP PGRI Nganjuk Economics Education - Ragil Retno Palupi; Hari Wahyono; Ludi Wishnu Wardana (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Most economic education students at STKIP PGRI Nganjuk feel that the large selection of products when shopping online makes them monitor the product they will buy every day. If they don't buy the item they have seen in the online shop, there will be a feeling of regret, so they decide to buy the item even though not a need at that time. Therefore, research was conducted on financial literacy, amount of pocket money, and lifestyle on the consumption behavior of STKIP PGRI Nganjuk economics students. This study aimed to analyze the effect of financial literacy, amount of pocket money, and lifestyle on the consumption behavior of STKIP PGRI Nganjuk economics students.